Peran Mahasiswa MSIB Batch 4 dalam Corporate Social Responsibility Perusahaan Melalui Sembako Ramadhan Kepada Masyarakat di Sekitar PT Petrokimia Gresik - Putri Prastikasari; Siti Ning Farida (Jurnal Kabar Masyarakat, 2023)
Based on the Katadata.com survey, basic prices ahead of Ramadhan in Indonesia tend to increase as of March 17 2023. Seeing these conditions, the purpose of this community service, PT Petrokimia Gresik and its Certified Independent Study Internship students (MSIB) get around a Ramadhan Sembako program as a form of Corporate Social Responsibility (CSR) company. This program involved 6 East Java "Veteran" UPN students and PT Petrokimia Gresik CSR department staff with a target of 8 sub-districts around PT Petrokimia Gresik. The results achieved with this program are the fulfillment of the basic needs of the community in order to achieve sustainable economic activity in an industrial area.